Beliefs about writing and its teaching in Peruvian primary teachers (Revista Peruana de Investigación Educativa, 2017)
Although the number of studies of teachers’ beliefs has increased in recent years, little is still known on an international level about teachers’ beliefs regarding writing and how it is taught. Two different ways in which persons can understand writing are distinguished: as a process and as a product. At the same time, two different approaches to teaching of writing are distinguished: the communicative approach and the normative approach. In this context, this study was intended to find out what teaching characteristics are associated with teachers’ beliefs about teaching of writing, and to describe how teachers’ beliefs about writing are related with their beliefs about the way it is taught. For the analysis, were considered responses by 3629 primary teachers from all regions of Peru, who replied to several questionnaires during the administration of the Ministry of Education’s 2013 Sample-based Assessment. It was found that socio-demographic characteristics (age, work experience, teacher training) are not related or are weakly related (sex) with teachers’ teaching approach. It was also found that two theoretically incompatible teaching approaches coexist among teachers: the communicative approach and the normative approach. Also, through structural equations, it was found that beliefs about writing are good predictors of the teachers’ teaching approach. These findings have implications for teacher training.
Keywords: teacher cognition; writing; teachers’ beliefs